Global impact of COVID-19 on stroke care. Issue 5 (July 2021) - Nogueira, Raul G.; Abdalkader, Mohamad; Qureshi, Muhammed M.; Frankel, Michael R.; Mansour, Ossama Yassin; Yamagami, Hiroshi; Qiu, Zhongming; Farhoudi, Mehdi; Siegler, James E.; Yaghi, Shadi; Raz, Eytan; Sakai, Nobuyuki; et al.
Background: The COVID-19 pandemic led to profound changes in the organization of health care systems worldwide. Aims: We sought to measure the global impact of the COVID-19 pandemic on the volumes for mechanical thrombectomy, stroke, and intracranial hemorrhage hospitalizations over a three-month period at the height of the pandemic (1 March–31 May 2020) compared with two control three-month periods (immediately preceding and one year prior). Methods: Retrospective, observational, international study, across 6 continents, 40 countries, and 187 comprehensive stroke centers. The diagnoses were identified by their ICD-10 codes and/or classifications in stroke databases at participating centers. Results: The hospitalization volumes for any stroke, intracranial hemorrhage, and mechanical thrombectomy were 26, 699, 4002, and 5191 in the three months immediately before versus 21, 576, 3540, and 4533 during the first three pandemic months, representing declines of 19.2% (95%CI, −19.7 to −18.7), 11.5% (95%CI, −12.6 to −10.6), and 12.7% (95%CI, −13.6 to −11.8), respectively. The decreases were noted across centers with high, mid, and low COVID-19 hospitalization burden, and also across high, mid, and low volume stroke/mechanical thrombectomy centers. High-volume COVID-19 centers (−20.5%) had greater declines in mechanical thrombectomy volumes than mid- (−10.1%) and low-volume (−8.7%) centers (p < 0.0001). There was a 1.5% stroke rate across 54, 366 COVID-19 hospitalizations. SARS-CoV-2 infection was noted in 3.9% (784/20, 250) of all stroke admissions. Conclusion: The COVID-19 pandemic was associated with a global decline in the volume of overall stroke hospitalizations, mechanical thrombectomy procedures, and intracranial hemorrhage admission volumes. Despite geographic variations, these volume reductions were observed regardless of COVID-19 hospitalization burden and pre-pandemic stroke/mechanical thrombectomy volumes.